2018
DOI: 10.3390/vetsci5020051
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey for Infectious Agents Associated with Subfertility and Abortion in Dairy Cattle in Trinidad and Tobago, West Indies

Abstract: Despite frequent reports of subfertility and abortion in dairy cattle in Trinidad and Tobago (T&T), little is known about the potential infectious and non-infectious causes. This study set out to investigate possible infectious causes of reproductive problems by measuring the seroprevalence of four of the most significant reproductive pathogens in dairy cattle worldwide: Brucella abortus (B. abortus); Neospora caninum (N. caninum), Bovine Viral Diarrhoea virus (BVDV), and Infectious Bovine Rhinotracheitis viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…It is known that only seropositivity does not certainly associate with abortion in all conditions. It is important to identify the actual causes in the aborting sheep and goats and/ or in the aborted fetus or placental tissues to confirm the pathogen is accountable for abortion (Morris et al, 2018). This result is in line with the reports of Gebremedhin (2015) and Wubishet et al (2017), who reported that the risk of Brucella seropositivity was not associated with abortion.…”
Section: Discussionsupporting
confidence: 79%
“…It is known that only seropositivity does not certainly associate with abortion in all conditions. It is important to identify the actual causes in the aborting sheep and goats and/ or in the aborted fetus or placental tissues to confirm the pathogen is accountable for abortion (Morris et al, 2018). This result is in line with the reports of Gebremedhin (2015) and Wubishet et al (2017), who reported that the risk of Brucella seropositivity was not associated with abortion.…”
Section: Discussionsupporting
confidence: 79%
“…In 1968, Jamaica reported an unknown number of cases of BoHV‐1 (OIE‐HANDISTATUS II, 2005). A study carried out during 2018 in Trinidad and Tobago detected BoHV‐1 antigens in 23% of bulk milk samples from dairy cattle (Morris et al., 2018). A similar ELISA‐based study in Grenada reported a lower prevalence of BoHV‐1 in cattle (3.8%) and in sheep (0.42%) (Tiwari et al., 2016b).…”
Section: Dna Viruses Circulating In Terrestrial Animals In the Caribb...mentioning
confidence: 99%
“…This needs further investigations. Furthermore, precise role of the isolated virus (BoHV5/India/2018/Bhilwara), other infectious agents (bacterial/parasitic) or their coinfections [39][40][41][42][43] needs to be examined.…”
Section: Plos Onementioning
confidence: 99%